Catalão (GO): uma contribuição ao estudo de cidades médias - Pires, Cyntia Miguel (2009)
This study attempts to understand the importance of Catalão GO and its condition as a medium sized city. So, it gets together both perspectives: scientific community`s analysis on the issue of Brazilian medium sized cities and scholar`s opinion on this theme. For the last, this study goes deep on the history review of the city and applies to it a methodology elaborated by a team of researchers on medium sized cities (Medium Sized Cities Network ReCiMe). Economic dimension is a privileged side according to the methodology chosen because it sheds light to the comprehension of the role played by the economic agents in the intraurban space in Catalão city. In addition, this study identifies elements which help to clarify the idea of medium sized city based on the economic agents observed in the social and spatial environment of the research area. During my writing a literature review was set on both the medium sized cities and also on the economical development in Catalão from the 1970`s on. The next step brings data collection, systematization and analysis, together with interviews applied to citizen in Catalão. The third biggest GDP and the first HDI in Goiás, among other features, places Catalão as a clear medium sized city with regional and extra regional importance according to the methodology applied to this research.